2000
DOI: 10.1007/s004250000269
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of phosphoribulokinase activity by antisense RNA in transgenic tobacco: definition of the light environment under which phosphoribulokinase is not in large excess

Abstract: To test the hypothesis that the contribution of phosphoribulokinase (PRK) to the control of photosynthesis changes depending on the light environment of the plant, the response of transgenic tobacco (Nicotiana tabacum L.) transformed with antisense PRK constructs to irradiance was determined. In plants grown under low irradiance (330 micromol m(-2) s(-1)) steady-state photosynthesis was limited in plants with decreased PRK activity upon exposure to higher irradiance, with a control coefficient of PRK for CO2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…The large increase in the levels of CBC intermediates in between low and higher irradiance in C. reinhardtii contrasts with previous studies in vascular plants where CBC intermediates were mostly unchanged upon an increase in light intensity (Perchorowicz et al, 1981;Perchorowicz and Jensen, 1983;Badger et al, 1984;Heber, 1984, 1986;Paul et al, 2000). The reason for the quite stable levels of phosphorylated CBC intermediates in vascular plants is thought to be due to a tight regulation of P homeostasis, which is required to prevent P i limitation of photosynthesis (Sharkey et al, 1986;Paul and Foyer, 2001).…”
Section: Differences In the Regulation Of Phosphorylated Metabolite Lcontrasting
confidence: 57%
“…The large increase in the levels of CBC intermediates in between low and higher irradiance in C. reinhardtii contrasts with previous studies in vascular plants where CBC intermediates were mostly unchanged upon an increase in light intensity (Perchorowicz et al, 1981;Perchorowicz and Jensen, 1983;Badger et al, 1984;Heber, 1984, 1986;Paul et al, 2000). The reason for the quite stable levels of phosphorylated CBC intermediates in vascular plants is thought to be due to a tight regulation of P homeostasis, which is required to prevent P i limitation of photosynthesis (Sharkey et al, 1986;Paul and Foyer, 2001).…”
Section: Differences In the Regulation Of Phosphorylated Metabolite Lcontrasting
confidence: 57%
“…These results were later challenged by Winder and Nishio (12), who reported that photosynthesis inhibition correlated with Rubisco decline in Fe-restricted Beta plants, and by Paul et al (32), who observed that CO 2 fixation rates were not significantly affected until PRK activity declined below 10% of the WT levels in antisense tobacco plants. However, more detailed investigations on the same lines showed that PRK did exert significant control on photosynthesis when the transformants were grown under a low-irradiation regime similar to that used in our experiments (33). It is thus likely that both the decrease in Rubisco levels (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Using the antisense potato, it was shown that aldolase is not generally accumulated in excess in chloroplasts for CO 2 assimilation, in contrast to other enzymes that are highly regulated and are in considerable excess like Rubisco (Stitt and Schulze 1994), fructose-1,6-bisphosphatase (Koßmann et al 1994), and phosphoribulokinase (Paul et al 2000). As a result, decreased expression of aldolase induced strong suppression of photosynthesis in both low and high light.…”
Section: Regulation Of the Ndh-and Fd-dependent Psi Cyclic Electron Flowmentioning
confidence: 96%